2020
DOI: 10.1111/jocd.13457
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of olive leaf extract–containing cream for facial rejuvenation: A pilot study

Abstract: Background Olive leaf extract (OLE), a naturally extracted product from olive leaves, contains oleuropein and other bioactive phenolic compounds. Oleuropein was identified to have various medical properties. It was also found to inhibit the effects of both acute and chronic UVB‐induced skin damage as well as accelerate wound healing activity. Aims To evaluate the efficacy of olive leaf extract–containing cream on facial rejuvenation. Methods This is a prospective pilot study with a total of 36 participants, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Moreover, several previous studies have demonstrated the beneficial effects of DOLE, which, along with its aqueous solubility, provides an attractive candidate for further evaluation for the treatment of skin pigmentary disorders. A previous clinical study [38] showed that the application of a patented OLE-containing cream (SuperHeal™ O-Live Cream, PhytoCeuticals, Inc., Elmwood Park, NJ, USA) for two months led to facial rejuvenation; the authors attributed the effects to the photoprotective, antioxidant, and anti-inflammatory properties of OLE in the formulation. Although the melanin index was not changed from the baseline group, the authors further reported that 53% of the 36 study participants showed visual reduction in hyperpigmented facial spots.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several previous studies have demonstrated the beneficial effects of DOLE, which, along with its aqueous solubility, provides an attractive candidate for further evaluation for the treatment of skin pigmentary disorders. A previous clinical study [38] showed that the application of a patented OLE-containing cream (SuperHeal™ O-Live Cream, PhytoCeuticals, Inc., Elmwood Park, NJ, USA) for two months led to facial rejuvenation; the authors attributed the effects to the photoprotective, antioxidant, and anti-inflammatory properties of OLE in the formulation. Although the melanin index was not changed from the baseline group, the authors further reported that 53% of the 36 study participants showed visual reduction in hyperpigmented facial spots.…”
Section: Discussionmentioning
confidence: 99%
“…47 In terms of adverse effects, no cases of toxicity were reported, probably due to the fact that these products are not able to reach the dermal venous circulation. 48 In the same vein, Wanitphakdeedecha et al 49 described that the use of a facial cream enriched with olive leaf extract promotes facial rejuvenation by decreasing transepidermal water loss and wrinkles and improving hydration.…”
Section: Effects On Skin Ageingmentioning
confidence: 99%
“…In vivo: prospective pilot study with humans (women and men): after two months of applying the cream twice daily, transepidermal water loss was reduced, skin hydration was increased, wrinkles and skin texture improved. 49…”
Section: Olive Leaf Extract-containing Creammentioning
confidence: 99%
“…Moreover, this effect was correlated to the decrease of cutaneous inflammation and the antioxidant activity of olive phenolic compounds like HTyr. Wanitphakdeedecha et al (2020) conducted a study where SUPERHEAL TM O-Live Cream was applied twice daily for 2 months in thirty-six female volunteers. The reported results showed that the transepidermal water loss (TEWL) started to decrease and the skin hydration started to significantly increase 2 months after the beginning of the treatment.…”
Section: Topical Formulations Based On Olive Oil Industry By-productsmentioning
confidence: 99%